Asymmetrical Brain Plasticity: Physiology and Pathology. (1st February 2021) - Esteves, M.; Ganz, E.; Sousa, N.; Leite-Almeida, H.
Highlights: Functional asymmetries are necessary for cognitive and emotional function. Lateralized structural and functional adaptation can be observed throughout life. In physiological conditions, lateralized plasticity is necessary for CNS specialized functions. In pathological conditions, such plasticity can be adaptive or maladaptive, depending on the stimulus and age of onset. Mechanisms underlying left/right differences in plasticity remain elusive. Abstract: The brain is inherently asymmetrical. How that attribute, manifest both structurally (volumetric, cytological, molecular) as well as functionally, relates to cognitive function, is not fully understood. Since the early descriptions of Paul Broca and Marc Dax it has been known that the processing of language in the brain is fundamentally asymmetrical. Contemporary imaging studies have corroborated early observations, and have also revealed significant functional links to multiple other systems, such as those sub serving memory or emotion. Recent studies have demonstrated that laterality is both plastic and adaptive. Learning and training have shown to affect regional changes in asymmetry, such as that observed in the volume of the planum temporale associated with musical practice. Increasing task complexity has been demonstrated to induce recruitment of contralateral regions, suggesting that laterality is a manifestation of functional reserve. Indeed, in terms of cognitive function, successful aging is often associated with a reduction of asymmetrical activity. The goal of this review is to survey and critically appraise the current literature addressing brain laterality, both morphological and functional, with particular emphasis on the asymmetrical plasticity associated with environmental factors and training. The plastic recruitment of contralateral areas associated with aging and unilateral lesions will be discussed in the context of the loss of asymmetry as a compensatory mechanism, and specific instances of maladaptive plasticity will be explored.